2006
DOI: 10.1039/b513376a
|View full text |Cite
|
Sign up to set email alerts
|

Structure characterization of free-standing filaments drawn in the liquid crystal state

Abstract: Stable free-standing liquid filaments formed by some layered mesophases of bent-core mesogens are unique structures. Some of their physical properties have been analyzed in recent studies, but their microscopic structure and conditions for stability have still been unclear. We explore details of filament shapes and surface profiles of filaments drawn in liquid crystal phases of bent-core mesogens by AFM and SEM measurements, and we present a microscopic structure model. Conclusions on the stabilizing mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…[3] Examples include the twist-bend nematic phase [3][4][5] characterised by ambidextrous heliconical structure on 10-nm range without layering; the helical nanofilament phase [6] of 30-40 nm wide stack of twisted layers with about 100 nm half pitch and the so-called B7 material [7,8] that forms peculiar micrometre scale helical patterns and slender freely suspended filaments. [9][10][11][12][13][14] The amazing optical B7 textures attracted an intense research that lead to many important findings. [7][8][9]13,[15][16][17][18][19][20][21] Small angle X-ray scattering (SAXS) [7,16,19] studies revealed a number peaks [16,19] that can be indexed by a slightly oblique monoclinic 2D unit cell with a~3-5 nm and b~8-20 nm periodicities.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Examples include the twist-bend nematic phase [3][4][5] characterised by ambidextrous heliconical structure on 10-nm range without layering; the helical nanofilament phase [6] of 30-40 nm wide stack of twisted layers with about 100 nm half pitch and the so-called B7 material [7,8] that forms peculiar micrometre scale helical patterns and slender freely suspended filaments. [9][10][11][12][13][14] The amazing optical B7 textures attracted an intense research that lead to many important findings. [7][8][9]13,[15][16][17][18][19][20][21] Small angle X-ray scattering (SAXS) [7,16,19] studies revealed a number peaks [16,19] that can be indexed by a slightly oblique monoclinic 2D unit cell with a~3-5 nm and b~8-20 nm periodicities.…”
Section: Introductionmentioning
confidence: 99%
“…However, in those studies single fibres (or whole bundles) did not form spontaneously, but were pulled mechanically between two supports. It has been shown that in contrast to the case of a columnar-type B 7 phase, the fibres of SmCP and PM-SmCP phases have cylindrical form [6].…”
Section: Structures Of the B 7 Phase 791mentioning
confidence: 98%
“…Lamellar as well as columnar structures are encountered among the bent core ('banana') compounds. It has been shown that several mesophases such as SmCP (where P stands for polar), PM-SmCP (polarization modulated SmC) and B 7 can also form free-standing fibres [3][4][5][6]. Until now, microscopic textures associated with the B 7 phase ('B 7 texture') remained among the most mysterious patterns of the 'banana phases'.…”
Section: Introductionmentioning
confidence: 98%
“…In a number of experiments [3,4] it is observed that the crosssection of a fiber drawn in air is independent of its length. Assuming this the problem of describing a fiber is posed as a free boundary problem for the cross-section with its free energy per unit length based on the distinctive elastic (molecular packing) and electrostatic properties of bent core liquid crystals.…”
Section: Introductionmentioning
confidence: 97%